Dominance styles mediate sex differences in Dark Triad traits - Semenyna, Scott W.; Honey, P. Lynne (My University, 2015)
We sought to determine what styles of social dominance are associated with Dark Triad traits (i.e., narcissism, psychopathy, and Machiavellianism) and whether sex differences in Dark Triad traits are mediated by dominance styles measured by the Dominance and Prestige Scale, and the Rank Styles with Peers Questionnaire. Machiavellianism, psychopathy, and narcissism are strongly associated with dominance-striving, but only narcissism is consistently correlated with prestige-striving. Dark Triad traits are negatively correlated with coalition-building, but positively correlated with dominant leadership and ruthless self-advancement. Sex differences in Dark Triad traits were mediated by various dominance styles, but mainly by dominance-striving and ruthless self-advancement. These results suggest that particular styles of social dominance are utilized by both men and women with Dark Triad traits.
Keywords: narcissism; Machiavellianism; psychopathy; Dark Triad; dominance; sex differences